Perceptions of senior managers on the upper limits policy in the Polokwane Municipality, Limpopo Province - Mthombeni, Vheli (My University, 2017)
The purpose of the study was to examine the perceptions of senior managers on the upper limits policy for the remuneration of senior managers at Polokwane Municipality. In 2014 the Minister responsible for Cooperative Governance and Traditional Affairs in South Africa published a notice on the implementation of upper limits for the remuneration of senior managers across all municipalities in South Africa. The notice signified a new paradigm in the local government remuneration practice in the local government sphere. Local government remuneration in South Africa was characterised by lack of uniformity and negative public perceptions on the huge salaries that senior managers in local government earned. There are substantial variations in municipal salary structures and benefits, municipal managers’ salaries vary between R155 424 and R1, 3 million per year (National Treasury Local Government Budgets and Expenditure Review, 2001/02 – 2007/08). The South African media published stories articles on senior local government managers who earns more than the president of the republic. The public scrutiny on the remuneration in local government was compared to the standard of service delivery in their areas, and often there was no relationship between the remuneration of the senior managers and the performance of their municipalities. The implementation of the upper limits policy in 2014 meant that for the first time in the democratic South Africa, the remuneration of senior managers in local government was regulated. This meant a shift from a practice of senior manager’s negotiated remuneration to nationally regulated remuneration. The implementation of the Upper Limits policy had the potential of de-stabilising the local government sector in terms of senior manager’s recruitment, retention and availability of skills due to the low remuneration that the policy has introduced. v The research was conducted at Polokwane Municipality and the study sampled all senior managers of Polokwane Municipality. The researcher opted for a qualitative research approach and utilised semi-structured interview schedule to gather data. The research findings indicate that all senior managers (7) of Polokwane Municipality perceived the upper limits policy negatively and they were not in support of its implementation. The research indicated that the reasons for the negative perception was that the Upper Limits Policy was not properly introduced at Polokwane Municipality. The researcher recommends that Polokwane Municipality needs to formally introduce the Upper Limits Policy to senior managers. This needs to be done through conducting workshops on the policy.
Theses (MPA.) -- University of Limpopo, 2017
Keywords: Senior managers; Upper limits policy; Polokwane Municipality; Remuneration policies; Municipal policy; City planning; Municipal government by City manager